Linear Array Thinning with Cavity backed U-slot Patch Antenna using Genetic Algorithm - Novalia Pertiwi; Fannush Shofi Akbar; Eko Setijadi; Gamantyo Hendrantoro (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
In this paper, a thinned linear array with Cavity backed U-slot Patch has been investigated using the Genetic Algorithm to minimize peak sidelobe level and the number of antenna elements. One of the essential steps in the Genetic Algorithm method is a crossover, which uses the Paired Top Ten and Combined Top Five rules applied to the Cavity backed U-slot Patch antenna. The peak sidelobe level value is -18.63 dB with a array filling of 63.33% at the broadside angle using Combined Top Five rules. In Paired Top Ten, the peak sidelobe level value is -19.48 dB with a array filling of 70%. The two methods are still better as compared to a dense array. This study is essential in the development of radar technologies since it needs a low sidelobe level.